Redesigning corporate identity at Murut cultural centre in promoting the place / Sulipah Rinduan - Rinduan, Sulipah (Faculty of Art and Design, 2013)
This chapter gives the explanation about early process of the academic writing. This whole process consists of finding the redesigning corporate identity at Murut Cultural Centre in promoting the place. Then, to know the impact of new environmental graphic and also to promote Murut Cultural Centre as one the tourism attractions in Malaysia. Besides that, researcher will do the literature review for the studies and journals which are background research, objective and research methodology, analysis and findings, conclusion and finding. In each chapter, shall has a own purpose and contents. The purpose of this research is redesigning corporate identity at Murut Cultural Centre in promoting the place. Based on this study many thing to do through literature, references and review on written materials such as a journals, previous research reports, books, magazines, newspapers or via the internet to have a better understanding of research topic. Thus, references also involve acts, plans and data that are related to the study. Early reviews are also conducted in this stage to identify problems. This part also to know the statement of problem at Murut Culture Centre. So, any information obtained will be used as a reference to provide a form of questionnaire. This stage, researcher will state the research the objective and approach toward the solution of corporate identity to introduce Murut Culture Centre. Besides that, researcher will include the methodology to find the problems. This part is to conduct analysis with the data and information that has been collected .This stage is very important especially to reach the aim of the whole study as it may change the outcome of the research. This study also involves analyzing the feedback from the respondents. This chapter is a final stage of methodology shows results after all the analysis is done. This involves coming out with new concept or strategy implement on current condition. There will be some recommendation that will explain for improvement of the case study.